Comparative analysis of helmeted impact response of Hybrid III and National Operating Committee on Standards for Athletic Equipment headforms. (March 2016) - Cobb, Bryan R; Zadnik, Abigail M; Rowson, Steven
As advanced helmet testing methodologies are developed, the effect headform selection may have on the biomechanical impact response must be considered. This study sought to assess response differences between two of the most commonly used headforms, the Hybrid III and National Operating Committee on Standards for Athletic Equipment headforms, through a series of helmeted impact tests. A total of 180 pendulum impact tests were conducted with three impactor velocities and six impact locations. Test condition–specific significant differences were found between the two headforms for peak linear and angular accelerations (α = 0.05), although differences tended to be small. On average, the National Operating Committee on Standards for Athletic Equipment headform experienced higher peak linear (3.7 ± 7.8%) and angular (12.0 ± 21.6%) accelerations, with some of the largest differences associated with impacts to the facemask. Without the facemask impacts, the average differences in linear (1.8 ± 6.0%) and angular (9.6 ± 15.9%) acceleration would be lower. No significant differences were found in coefficient of variation values for linear (Hybrid III: 2.6 ± 2.3%, National Operating Committee on Standards for Athletic Equipment: 2.0 ± 1.4%) or angular (Hybrid III: 4.9 ± 4.0%; National Operating Committee on Standards for Athletic Equipment: 5.2 ± 5.8%) acceleration. These data have application toward development and validation of future helmet evaluation protocols and standards.